Buying the vote a history of campaign finance reform - Mutch, Robert E. (Oxford University Press, 2014)
Campaign finance reform has always been motivated by a definition of democracy that does not count corporations as citizens and holds that self-government works best by reducing political inequality. In the early years of the twentieth century, Congress recognized the strength of these principles by prohibiting corporations from making campaign contributions, passing a disclosure law, and setting limits on campaign expenditures. These reforms were not controversial at the time, but conservative opposition to them appeared in the 1970s.